Ray Donovan. Season four [videorecording (DVD)] - Schreiber, Liev; Malcomson, Paula, 1970-; Marsan, Eddie (CBS DVD ; Paramount Home Entertainment, 2016)
One of the most critically acclaimed dramas on television is back with its most exciting season yet! After the bloody Minassian shootout, Ray Donovan is focused on healing himself and his damaged relationship with his family. But Ray is soon pulled back into his old life by a troubled boxer and an enigmatic art dealer with ties to the Russian mafia.